2007
DOI: 10.1007/s00259-007-0622-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and radiation dosimetry of the norepinephrine transporter radioligand (S,S)-[18F]FMeNER-D2: a human whole-body PET study

Abstract: Based on the distribution and dose estimates, the estimated radiation burden of (S,S)-[(18)F]FMeNER-D(2) is lower than that of [(18)F]FDG. The radioligand would allow multiple PET examinations in the same research subject per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The rapid elimination of radioactivity from blood following 123 I‐NKJ64 injection supports the efficient delivery of the radiotracer to the tissues. Radioactivity rapidly entered the lungs, reaching a maximum of 6% of injected dose consistent with previous reports of significant lung uptake for other NAT radiotracers (Kanegawa et al,2006; Kiyono et al,2004; Kung et al,2004; Lakshmi et al,2008; McConathy et al,2004; Takano et al,2008a). Both Kiyono et al (2004) and Kanegawa et al (2006) reported significant uptake in the lungs of 125 I‐MIPP and 125 I‐IPBM, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The rapid elimination of radioactivity from blood following 123 I‐NKJ64 injection supports the efficient delivery of the radiotracer to the tissues. Radioactivity rapidly entered the lungs, reaching a maximum of 6% of injected dose consistent with previous reports of significant lung uptake for other NAT radiotracers (Kanegawa et al,2006; Kiyono et al,2004; Kung et al,2004; Lakshmi et al,2008; McConathy et al,2004; Takano et al,2008a). Both Kiyono et al (2004) and Kanegawa et al (2006) reported significant uptake in the lungs of 125 I‐MIPP and 125 I‐IPBM, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…[ 18 F] 8 is labeled in a fluoromethoxy position which may be susceptible to radiodefluorination in human subjects in vivo to give high radioactivity uptake in bone including skull. Skull uptake of radioactivity is known to occur for other PET radioligands labeled with fluorine-18 in a fluoromethoxy position, including ( S , S )-[ 18 F]FMeNER-D 2 35 and [ 18 F]FMEPEP- d 2 36 . In fact the incorporation of deuterium into these radioligands is intended to counter radiodefluorination in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…The difference might be due to different doses and route administration of the blocking drug (nisoxetine): 2mg/kg (intravenous) vs. 10mg/kg (intraperitoneal) and/or due to the different fundamental pharmaceutical properties of these two tracers. On the other hand, a high lung uptake in human of another MRB derivative, (S,S)-[ 18 F]FMeNER-D2, was reported [20]. Its high lung accumulation was considered to be non-specific due to high-affinity amine binding sites in the macrophages in the lungs.…”
Section: Discussionmentioning
confidence: 99%